Chemical Prevention and Control of the Green Tide and Fouling Organism Ulva: Key Chemicals, Mechanisms, and Applications - Tang, Tao; Effiong, Kokoette; Hu, Jing; Li, Chao; Xiao, Xi (Frontiers in Marine Science, 2021)
The green algae, Ulva spp., have been causing environmental problems worldwide, e.g., green tides and biofoulings. Green tides resulted from bloom floating Ulva have caused substantial economic losses. Ulva foulings increase the maintenance cost of marine facilities and contribute to the biomass of floating algae. Chemical methods are generally very inexpensive and convenient for suppression of Ulva spp. during their early life stages, thus solving the green tide and fouling problem at the source. In this paper, classical chemical methods that have been or are in use and emerging chemical methods under research are systematically reviewed. The advantages, disadvantages, mechanisms, and applications of these methods are also summarized. Highly toxic reagents are used in classical chemical methods, including oxidants, acids, heavy metal compounds, and synthetic biocides directly used or applied in antifouling coatings to kill or inhibit Ulva effectively. However, these toxic reagents have a high risk of resulting in secondary environmental problems. In order to minimize other environmental impacts while solving the current problem, emerging, and environmentally friendly chemical methods have been developed, such as the utilization of degradable natural products (mainly allelochemicals) and semi-natural products for Ulva inhibition and fouling control, and the use of flocculating agents to prevent microscopic propagules from germinating. All these chemical methods provide a promising direction for the prevention and control of Ulva.